Price Rigidity in Norway in the Nineteenth Century - Visockytė, Ligita (Ekonomika, 2018)
This paper analyzes nominal price development in Norway from 1830 to 1920 and fills a gap in the literature on nominal price rigidity in Europe during the nineteenth and the beginning of the twentieth centuries. The research question: how did the nominal price rigidity change in Norway during this time period? The focus on Norway is justified because of the availability of historical data and gaps in literature concerning the nominal rigidities.The analysis of some of the digitized data for Oslo, Bergen and Stavanger during the period of 1830–1913 indicate that: a) The flexibility of prices did not change much during the classical Gold Standard in Norway; b) The change in price rigidity mainly came because of the changing magnitude of price changes; c) The decrease in magnitude might have happened before the Gold Standard took effect in Norway.
Keywords: price rigidity, nominal rigidity, Norway